Virtual learning environments and skills development in times of pandemic - López-Sánchez , Jorge Luis (2021)
The pandemic caused by COVID-19, which has been affecting humanity since March 2020, has forced universities to suspend the development of academic activities within their facilities as a measure to prevent the contagion and spread of the virus. Under these circumstances, the possibility of adapting teaching systems through virtual learning environments (VLE) arose. For this to be successful, the necessary technological resources must be available, and universities, teachers and students must be equipped with the necessary equipment.